Small Prose of Y. Mamleev: Tradition or Anti-tradition - L. G. Khoreva (Научный диалог)
The features of the interpretation of philosophical questions, traditional motifs and plots in the short prose of Yu. Mamleev are considered. The relevance of the study is due to the emergence of a large number of studies devoted to Y. Mamleev, but insufficient analysis of the nature of traditional and / or anti-traditional aspects in the writer's prose. An overview of the concepts of “cultural tradition” and “cultural anti-tradition” in the works of domestic and foreign researchers is offered. The author considers the concepts of “counter-tradition” and “anti-tradition”, gives the definition of cultural studies, comes to the conclusion about a single genesis of tradition and anti-tradition, unlike tradition and counter-tradition. Reference to this material is the novelty of the study. The author comes to the conclusion that the work of Mamleev, despite the new interpretation of the Russian idea he declared, continues the traditions of Gogol and Dostoevsky. It is shown that the questions risen by Mamleev, and their solutions, as well as the presented interpretations of philosophical systems should be considered in line with the principles of anti-tradition, creating its own world, different from the traditional one, which awakens new feelings and emotions in the reader, but raises and solves questions that were raised by Gogol and Dostoevsky.